Implikasi Teori Konflik Fungsional: Tinjauan Pemikiran Tokoh Lewis A Coser di MIS Al-Azhar Jember - Nadilla Aleyda Maqhfira Agustin; Moch Ayyub Sholah Baldani; Mu’alimin Mu’alimin (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research discusses the implications of functional conflict theory reviewing the thoughts of Lewis A. Coser in MIS Al-Azhar Jember. The functional conflict theory perspective in schools does not always have a negative impact, but also has a positive function for students socially. The method used in this research is a qualitative method with data sources obtained through in-depth interviews, documentation and literature study. The observations made by the researcher involve implications for handling strategies based on functional conflict theory. This research aims to find out the implications of functional conflict theory regarding the thoughts of Lewis A. Coser in MIS Al-Azhar Jember. The research results show that there are sources and strategies for handling conflict as well as the implications of functional theory. The results of the collaboration strategy service carried out by the school show that there is cooperation involving both parties participating in resolving the conflict.